(untitled) (Nigerian Journal of Technology, 2021)
In this study, municipal plastic waste is used in producing paving blocks. Binders in the form of melted waste plastic bottles (Polyethelene Terephthalate (PET)) and water sachets (High Density Polyethylene (HDPE) with river sand, were used in making the blocks. Mix ratios; 1:1, 1:1.5 and 1:2 of sand-plastic waste were considered. Sand-cement mixes were adopted as the controls. 230mm x 140mm x 55mm blocks were cast, cured in water at ambient temperature and tested for 72-hours for water absorption and 21 days compressive strength. 3 specimen were prepared for each mixture. Sand-HDPE mix produced stronger blocks than sand-PET and sand-cement mixes. Topmost compressive strength of 17N/mm2 was generated from sand-HDPE mix of 1:2. Sand-PET blocks should be avoided since they generate very low strengths. Sand-plastic waste blocks melt faster at higher temperatures. Therefore, plastic paving blocks can only be used for light load pavements not subjected to high temperature.